Neoliberalismo, Neodesarrollismo y Socialismo bolivariano. Modelos de desarrollo y Políticas públicas en América Latina - Vidal Molina, Paula (Ariadna Ediciones, 2019)
This book includes a set of papers on the political and economic development problems that have occurred in Latin America in recent decades.